PENGARUH PENGGUNAAN LAPISAN EDIBEL (EDIBLE COATING), KALSIUM KLORIDA, DAN KEMASAN PLASTIK TERHADAP MUTU NANAS (Ananas comosus Merr.) TEROLAH MINIMAL - Indera Sakti Nasution; Yusmanizar Yusmanizar; Kurnia Melianda (Jurnal Teknologi dan Industri Pertanian Indonesia, 2012)
The problem that often occurs before consuming fresh pineapple is it takes a long time to peel the pineapple. Minimal processing of pineapple is one of the solutions for practical use by consumers who would like to consume it fresh. However, minimally processed pineapple will be easily damaged and has short shelf life. The aims of this study are to determine the quality of minimally processed pineapple coated with edible coating, effect of calcium chloride dipping, as well as plastic packaging at low temperatures storage. Combination of Cassava starch and glycerol used as edible coating for pineapple dipped in CaCl2for 1 minute and 2 minutes, respectively. Products were packaged using polyethylene, polypropylene, and without packaging. It is obtained that dipping the product in CaCl2 for 2 minutes and packaging it using polypropylene (plastic) can prolong the shelf life of minimally processed pineapple stored at 5°C up to 8 days.